Syn-deformational remanent magnetization of the Mount Eclipse Sandstone, central Australia - Li, Z. X.; Powell, C. McA.; Schmidt, P. W. (Geophysical Journal International, 1989)
The palaeomagnetism of the latest Devonian-Early Carboniferous Mount Eclipse Sandstone in central Australia reveals samples from 16 out of 31 sites having a consistent hightemperature component of natural remanent magnetization. Site-mean directions from the two limbs of the most detailed studied syncline attain their best grouping after 75 per cent of ‘unfolding’, and further ‘unfolding’ causes a ‘cross-over’ feature. Mineralogical studies using microscope and electron microprobe show that this remanance is most likely to be carried by secondary haematite formed by alteration of Fe-rich minerals during the midCarboniferous deformation. Four different models are examined to reconstruct the palaeohorizontal for the syn-deformational remanence. The best estimate of the palaeomagnetic South Pole position is lat. = 33.8°S, and long. = 121.2°E (dp = 19.2°, dm = 19.7°), close to Australia. This result indicates a rapid polarward movement of eastern Gondwanaland during the first half of the Carboniferous. We also suggest that the widespread Alice Springs Orogeny-related overprints in central Australia were acquired during the beginning of the main phase of deformation in the mid-Carboniferous.